Conflict, Nutritional Status and Patterns of Young Child Feeding: An in-depth analysis - Abul-Fadl, Azza M.A.; Al-Jawaldeh, Ayoub; AlYassin, Samaah (International Journal of Scientific Research and Management (IJSRM), 2019)
Background: Malnutrition in countries of the Eastern Mediterranean region (EMR) impedes their development. Aim: To study patterns of complementary feeding (CF) and continued breastfeeding (CBF) on nutritional status and deaths from micronutrient deficiencies (MDs) in EMR countries. Methods: Data from ten EMR countries were compiled using UNICEF Global expanded health survey (2018). Data included EBF, CBF rates. CF core indicators included introduction of soft and semi-solid and solid food (ISSS) at 6-8 months, minimum acceptable diet (MAD), minimum dietary diversity (MDD) and minimum meal frequency (MMF). Analysis was done in relation to age, sex, residence, wealth quintiles, maternal education, anemia, stunting and wasting in children under-five of age (CU5) and deaths from MDs. Results: CBF was higher in the uneducated, poor and rural areas. MMF, MDD and MAD increased significantly by education and higher wealth quintiles and urban residence (P